2001
DOI: 10.1021/jp011265i
|View full text |Cite
|
Sign up to set email alerts
|

In2S3 Nanocolloids with Excitonic Emission:  In2S3 vs CdS Comparative Study of Optical and Structural Characteristics

Abstract: Stable aqueous colloids of 2-3 nm In 2 S 3 nanocrystals have been prepared by using the classical method of nanoparticle stabilization by low molecular weight thiols. TEM crystal lattice spacing, X-ray diffraction, EDAX data, and electron diffraction indicate that the nanoparticles are predominantly in -In 2 S 3 form. They exhibit relatively strong excitonic emission at 360-380 nm with a quantum yield of 1.5%. The excitonic radiative lifetime is 350 ns, which indicates that a direct allowed electronic transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
100
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 73 publications
6
100
0
1
Order By: Relevance
“…In addition, the UV/Vis spectra of nanoplates showed a steplike shape, which was mentioned to be an indicator of conduction and valence band transition in b-In 2 S 3 . [20] Interestingly, we observed no significant differences between the UV/Vis spectra of 63-, 45-, 33-, and 22-nm nanoplates (see Supporting Information for UV/ Vis spectra of 63-, 45-, and 22-nm nanoplates), which implies that the sizes (22-63 nm) of the nanoplates are beyond the quantum confinement range. Detailed optical characterizations including emission, quantum yields, and decay kinetics will be reported elsewhere.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…In addition, the UV/Vis spectra of nanoplates showed a steplike shape, which was mentioned to be an indicator of conduction and valence band transition in b-In 2 S 3 . [20] Interestingly, we observed no significant differences between the UV/Vis spectra of 63-, 45-, 33-, and 22-nm nanoplates (see Supporting Information for UV/ Vis spectra of 63-, 45-, and 22-nm nanoplates), which implies that the sizes (22-63 nm) of the nanoplates are beyond the quantum confinement range. Detailed optical characterizations including emission, quantum yields, and decay kinetics will be reported elsewhere.…”
mentioning
confidence: 74%
“…Figure 3 b shows a representative UV/Vis absorption spectrum of 45-nm hexagonal nanoplates. Compared to the absorption peak of 3.0-nm nanoparticles, [20] that of 45-nm nanoplates was red-shifted by 30 nm. In addition, the UV/Vis spectra of nanoplates showed a steplike shape, which was mentioned to be an indicator of conduction and valence band transition in b-In 2 S 3 .…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…34,35 These latter materials will directly form a metal sulfide solid upon reaction with the reactive sulfur, likely H2S, formed by the enzymatic turnover of L-cysteine by the putative cystathio-nine γ-lyase class CSE enzyme. 28 In contrast, reaction with indium nitrate forms a relatively stable species with a charac-teristic absorption peak at 290 nm, which has previously been identified as a molecular cluster of indium and sulfur, 46 rather than bulk or nanocrystalline In2S3. A similar result is obtained upon addition of Na2S to a mixture of indium nitrate with L-cysteine, whereas a bulk precipitate of In2S3 likely combined with indium hydroxide is formed in the absence of L-cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that its intensity and position with respect to the main peak is affected by the choice of stabilizer and by the media (37). The closeness of the emission peaks to the absorption onset of the semiconductor indicates that this emission comes from the interband electron-hole recombination.…”
Section: Optical Propertiesmentioning
confidence: 99%